Pengaruh Investment Opportunity Set dan Penerapan Good Corporate Governance Terhadap Kualitas Laba - Dwi Putri Aningrum; Ade Imam Muslim (Wahana Riset Akuntansi, 2020)
This research aims to investigate the effect of the investment opportunity set and the implementation of good corporate governance on earnings quality. The observations in this research amounted to 75 data from manufacturing companies listed on the IDX in 2015-2019 that have met the purposive sampling criteria. Based on the results of panel data regression, it is concluded that the investment opportunity set and the implementation of good corporate governance have a significant effect simultaneously on earnings quality. Partially, the investment opportunity set and managerial ownership have no effect on earnings quality. Meanwhile, institutional ownership and independent board of commissioners have a significant negative effect on earnings quality.Keywords: Investment Opportunity Set; Managerial Ownership; Institutional Ownership; Independent Board of Commissioners; Earnings Quality.